Vitamin D receptor (VDR) gene polymorphisms and genetic susceptibility to thyroid cancer - Xavier, David André Rodrigues (2014)
Thyroid cancer is the most common endocrine malignancy and a complex disease with a largely unknown aetiology. Thyroid carcinomas are derived from thyroid follicular cells and parafollicular cells. The majority of thyroid cancer cases comprise both papillary (PTC) and follicular carcinomas (FTC). The evaluation of genetic susceptibility could give valuable information regarding the risk of thyroid cancer development. There are many genes associated with the thyroid function that modulates the risk of tumour development. Among them, is the vitamin D receptor gene (VDR), located on chromosome 12q12-q14, and includes eight protein coding exons (exons 2-9) and one untranslated exon (exons 1a-1f). The most common VDR polymorphisms investigated are FokI (rs10735810 C>T), located in exon 2 of VDR, BsmI (rs1544410 G>A) and ApaI (rs7975232 G>T), located in intron 8, and TaqI (rs731236 T>C), located in exon 9 of VDR. The importance of vitamin D and its receptor VDR, in many signalling pathways is well known. Therefore we aim to verify in which way VDR polymorphisms influence the predisposition for thyroid cancer development. The contribution of four well-known VDR polymorphisms (FokI, BsmI, ApaI and TaqI) for the genetic susceptibility of thyroid cancer in the Portuguese population was analysed, including haplotypes comparisons. The following parameters were studied: thyroid cancer type differences (PTC vs. FTC), age (≤45 vs. >45 years), gender (male vs. female), carcinoma size (≤10mm vs. >10mm), lymph node metastasis and distant metastasis multicentricity, and stage of cancer (I-II vs. III-IV). All the participants in the study were Caucasian Portuguese inhabitants, being subdivided into two groups: patients with thyroid cancer (N = 208) and a control group (N = 248). In conclusion, there were some statistically significant differences in some parameters assessed. However, the results considered were only those with a statistical significant p-value < 0.005, according to Bonferroni’s correction. Therefore, the results suggest that BsmI polymorphism genotype AA (p = 0.004) may influence lymph node metastasis or distant metastasis in patients with DTC. Moreover, the TT genotype (p = 0.004) of ApaI polymorphism may increase the predisposition for more aggressive phenotypes of DTC, since it is overrepresented in patients with more advanced cancer stages (III-IV).